The young man and his responsibility - Hulett, M. F. (My University, 1893)
Introduction: The young man of today enters upon his life work with extraordinary possibilities. Positions of trust greater than has before been assumed by mankind are extended in every direction in search of persons competent to take them. The accumulations of past ages: advances in science, art, literature, and economic statesmanship have contributed a responsibility of such magnitude that it is with no small feeling of anxiety that he assumes the duties of citizenship.
Citation: Hulett, M. F. The young man and his responsibility. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Advancements; Science; Art; Responsibility; Citizenship; Theses; Manuscripts (documents)